UPAYA DOSEN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER MAHASISWA AGAR RAJIN IBADAH DI AKADEMI FARMASI - Zul Efendi (JIP: Jurnal Ilmu Pendidikan, 2023)
Islamic religious education is something highly important in shaping an individual's character. Its guidance and teachings are directed towards instilling a wholehearted belief in the existence of God, fostering obedience and submission in carrying out His commandments through worship, and cultivating noble morals. By studying Islamic religious education, it is hoped that an individual can internalize these values, leading to their manifestation in everyday behavior. Additionally, Islamic religious education can prevent someone from engaging in wrongful deeds. The application of Islamic Education involves an increase in piety towards the One God, and noble character is a manifestation of the faith embraced by each individual. Therefore, when faith and piety are integrated within a person, it prevents them from engaging in destructive, defamatory, and harmful actions to society, which could pose serious threats to the unity and future of the nation. Islamic Education is crucial in shaping and developing students' characters. Religious and moral education must mutually integrate and interact within the evolving social realities in the community. Education that incorporates religious values ultimately has the potential to mold individuals holistically.